2003
DOI: 10.1080/1071576031000097526
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulates Functional Capacities of Polymorphonuclear Neutrophils

Abstract: Recent studies report that leptin may be able to modulate some functions of cells involved in non-specific immune response. We recently found that a functional leptin receptor is present on polymorphonuclear neutrophils (PMNs) and may be able to influence their oxidative capacities. We demonstrate here for the first time that leptin is also able to stimulate chemotaxis of PMNs and exerts by itself a chemoattractive effect comparable to that of well-known formyl-methionyl-leucyl-phenylalanine, and a stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 25 publications
6
125
2
3
Order By: Relevance
“…The characteristics were consistent with the results reported by Zarkesh-Esfahani et al [23] showing that leptin has no direct effect on human PMN activation, and also those by Ottonello et al [17] demonstrating that leptin shows no secretagogue properties such as superoxide production in human PMN. However, these are rather conflicting with the reports by Caldefie-Chezet et al [4,5] who demonstrated that leptin is capable of inducing hydrogen peroxide and enhancing PMA-induced superoxide produc- Fig. 3.…”
Section: (A) (B) (C) (D)contrasting
confidence: 55%
See 1 more Smart Citation
“…The characteristics were consistent with the results reported by Zarkesh-Esfahani et al [23] showing that leptin has no direct effect on human PMN activation, and also those by Ottonello et al [17] demonstrating that leptin shows no secretagogue properties such as superoxide production in human PMN. However, these are rather conflicting with the reports by Caldefie-Chezet et al [4,5] who demonstrated that leptin is capable of inducing hydrogen peroxide and enhancing PMA-induced superoxide produc- Fig. 3.…”
Section: (A) (B) (C) (D)contrasting
confidence: 55%
“…It is demonstrated in human PMN that leptin is capable of enhancing PMA-induced superoxide production and of stimulating chemotaxis and hydrogen peroxide production without modification of phagocytosis [4,5]. Partially contradictory to these reports, Ottonello et al [17] showed that leptin is a pure chemoattractant for human PMN, without having secretagogue properties such as superoxide production.…”
mentioning
confidence: 89%
“…Paradoxically, obese subjects present strongly decreased levels of circulating adiponectin (Arita et al 1999, Matsubara et al 2002. Leptin is a 16 kDa polypeptide hormone encoded by the obese gene (Zhang et al 1994) that is involved in the regulation of energy balance (De Vos et al 1995), reproduction, and immunity (Mounzih et al 1997, Caldefie-Chezet et al 2003, and acts as a proinflammatory factor (Lago et al 2007). Despite the numerous nonadipose sources described (Mix et al 2000, Solberg et al 2005, the main source of leptin in the body remains adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism by which leptin may modulate trafficking of neutrophils in response to these triggers including CS is the induction of neutrophilic chemokines, such as CXCL1, by resident lung cells. In addition, leptin itself has been described to be a chemoattractant for neutrophils (11,41). On the contrary, leptin is known to reduce expression of neutrophil chemoattractants and inhibits neutrophil migration in response to classical chemoattractants (41,42).…”
Section: Figurementioning
confidence: 99%
“…Recently published studies demonstrate that leptin has a potentiating role in the function of both innate and adaptive immunity (10), making it an ideal candidate for a role in chronic inflammatory airway diseases such as COPD. On neutrophils and macrophages, leptin stimulates chemotaxis (11) and enhances functional capacities, such as oxidative burst (11), phagocytosis (12), and cytokine secretion (13,14). In addition, leptin exerts proliferative (15) and antiapoptotic effects (16) on T lymphocytes and promotes Th1 cell differentiation (17).…”
mentioning
confidence: 99%